Solar Cells: Overcoming the Ambient Manufacturability‐Scalability‐Performance Bottleneck in Colloidal Quantum Dot Photovoltaics (Adv. Mater. 35/2018). Issue 35 (26th August 2018) - Kirmani, Ahmad R.; Sheikh, Arif D.; Niazi, Muhammad R.; Haque, Md Azimul; Liu, Mengxia; de Arquer, F. Pelayo García; Xu, Jixian; Sun, Bin; Voznyy, Oleksandr; Gasparini, Nicola; Baran, Derya; Wu, Tom; et al.
Abstract : The low‐cost fabrication of colloidal‐quantum‐dot (CQD) solar cells in ambient air remains elusive in many parts of the world due to high humidity. In article number 1801661, Aram Amassian and co‐workers demonstrate a simple oxygen‐doping step that enables ambient manufacturing, irrespective of seasonal humidity variations, to obtain solar cells with power conversion efficiency > 10% by blade‐coating in air at industrially viable speeds. Cover by Heno Hwang, scientific illustrator, KAUST.